How does the brain deal with cumulative stress? A review with focus on developmental stress, HPA axis function and hippocampal structure in humans - FRODL, THOMAS; O'KEANE, VERONICA (My University, 2012)
There is evidence that excessive stress exposure of the brain, mediated through the neurotoxic effects of cortisol and possibly neuroinflammation, causes damage to brain structure and function: the glucocorticoid cascade hypothesis. Functional changes of hypothalamic-pituitary-adrenal (HPA) axis as well as alterations in brain structures like the hippocampus have been consistently reported in major depression. However, there has not been a lot of emphasis on bringing findings from studies on early childhood stress, HPA axis functioning and hippocampal imaging together. This is the subject for this systematic review of the literature on how developmental stress, specifically childhood maltreatment, may impact on HPA axis function and hippocampal structure. We will also review the literature on the relationship between HPA axis function and hippocampal volume in healthy, depressed and other disease states. There is evidence that prenatal stress and childhood maltreatment is associated with an abnormally developing HPA system, as well as hippocampal volume reduction. Smaller hippocampal volumes are associated with increased cortisol secretion during the day. We conclude that a model integrating childhood maltreatment, cortisol abnormalities and hippocampal volume may need to take other factors into account, such as temperament, genetics or the presence of depression; to provide a cohesive explanation of all the findings. Finally, we have to conclude that the cascade hypothesis, mainly based on preclinical studies, has not been translated enough into humans. While there is evidence that early life maltreatment results in structural hippocampal changes and these are in turn more prominent in subjects with higher continuous cortisol secretion it is less clear which role early life maltreatment plays in HPA axis alteration.
PUBLISHED
doi: 10.1016/j.nbd.2012.03.012
Keywords: Neuroscience; Major depressive disorder; Stress; cortisol; MRI; hippocampus; childhood maltreatment; dexamethason suppression test; DST; CAR; Neuroscience